G377 New models of care for children: testing integrating primary and secondary care clinics. (12th March 2018) - Goodwin, R; Lemer, C; Satherley, R; Wolfe, I
Abstract : Aims: Integrated General Practitioner-Paediatrician 'In-Reach' clinics aim to improve access to care and professional learning across primary-secondary care. The aim of this pilot project is to understand the range of presenting conditions and outcomes among children referred by General Practitioners (GP) to GPs-Paediatrician 'In-Reach' clinics, instead of hospital outpatients'. Methods: Retrospective case review of 101 patient's notes. Cases identified through an electronic search of consultations during a 6 month period in 2017. 202 cases were identified, listed alphabetically by patient surname, and alternate records were chosen systematically for inclusion. A senior clinician identified the presenting problem using ICD10 codes grouped into tier one categories, and clinic outcomes. Results: Our sample comprised 101 children (0–18 years) presenting with 115 problems. Constipation, eczema, and asthma accounted for 25% of problems. The top 5 ICD10 categories, representing 60% of the total, were digestive, dermatological, musculoskeletal, nervous, and respiratory problems ('other' comprised a large range of conditions each with small numbers of patients) (table 1). Nearly a third of problems required only reassurance, one in five required a prescription, and a specialist referral was made for 24% of children seen (table 2). Conclusion: A substantial proportion of children had common problems requiring reassurance or simple management in primary care. Specialist referral was required for 24% of children. If this sample is representative, approximately three quarters of children, who would otherwise have been referred for hospital outpatients' appointments, could be seen and managed with support in primary care settings. These preliminary results suggest that integrating care across the primary-secondary care interface could help improve access to care.